Risk Factors for Skin Injuries in Hospitalized Children: a Retrospective Study - Biagio Nicolosi; Eustachio Parente; Irene Fontani; Sabina Idrizaj; Daiana Stringi; Claudia Bamonte; Yari Longobucco; Emanuele Buccione; Marina Maffeo; Valentina Granai; Mirco Gregorini; Daniele Ciofi (Infermieristica Journal, 2024)
Background. Skin injuries in hospitalized pediatric patients can slow recovery, increase infection risk, pain, stress, length of stay, and healthcare costs, while reducing family quality of life. The prevalence and incidence of these injuries vary by environment, comorbidities, and specific pathologies.